2023
DOI: 10.1002/asia.202201181
|View full text |Cite
|
Sign up to set email alerts
|

Notable Catalytic Activity of Transition Metal Thiolate Complexes against Hydrosilylation and Hydroboration of Carbon‐Heteroatom Bonds

Abstract: Chemists tend to use transition metal hydride complexes rather than thiolate complexes to catalyse chemical transformations because the hydride complexes possess diverse catalytic reactivity, although most of them are air/ moisture-sensitive and difficult to prepare. By comparing the catalytic performances of pincer ligated group 10 metal thiolate and hydride complexes in catalysing the hydroboration and hydrosilylation of C=O and C=N bonds, we demonstrate in this review that transition metal thiolate complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…20 Interestingly, it has also been reported that metal thiolate complexes are better catalysts than metal hydride complexes. 21 Chen and coworkers reported that the nickel thiolate complex 16 is a better catalyst than the nickel hydride complex 22 containing the same pincer ligand for the hydroboration of CO 2 to methanol. Similarly, the Pt(II) thiolate complexes containing the bis(phosphinite) pincer are far better catalysts than the same ligand coordinated Pt(II) hydride complexes for the hydrosilylation of aldimines to amines.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Interestingly, it has also been reported that metal thiolate complexes are better catalysts than metal hydride complexes. 21 Chen and coworkers reported that the nickel thiolate complex 16 is a better catalyst than the nickel hydride complex 22 containing the same pincer ligand for the hydroboration of CO 2 to methanol. Similarly, the Pt(II) thiolate complexes containing the bis(phosphinite) pincer are far better catalysts than the same ligand coordinated Pt(II) hydride complexes for the hydrosilylation of aldimines to amines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Li and coworkers reported the hydrosilylation of aldehydes and ketones with 2 mol % of iron complex containing bidentate P,S-thiolate ligands . Interestingly, it has also been reported that metal thiolate complexes are better catalysts than metal hydride complexes . Chen and coworkers reported that the nickel thiolate complex is a better catalyst than the nickel hydride complex containing the same pincer ligand for the hydroboration of CO 2 to methanol.…”
Section: Introductionmentioning
confidence: 99%
“…High conversions and good isolated yields were observed in most cases. The reaction generally proceeded faster with aldehydes when compared to ketones, as typically observed in the hydrosilylation of carbonyl compounds [53][54][55][56]. In an intermolecular competition reaction between PhCHO and PhCOMe with PhSiH3 (1:1:1 molar ratio), PhCHO conversion reached 89% within 3 h while only <5% PhCOMe reacted.…”
Section: Catalytic Hydrosilylationmentioning
confidence: 68%
“…Among these developments, manganese-catalyzed hydrosilylation occupies a special place, thanks to the early work by the Cutler group, showing that simple manganese carbonyl complexes were effective catalysts for the hydrosilylation of various unsaturated substrates [47][48][49][50][51][52]. Hydrosilylation of C=O-containing compounds represents a mild and versatile approach for the reduction of these compounds and various metal and nonmetalcatalyzed reactions have been reported using commercial hydrosilane reagents [53][54][55][56]. Not surprisingly, recent research in manganese also provides a wide range of catalysts for the hydrosilylation of aldehydes, ketones, esters, amides, and carboxylic acids [57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a number of organometallic complexes based on first-row transition metals (M = Mn, Fe, Co, Ni, Cu, Zn) have been recently demonstrated to catalyze regioselective hydrosilylation and/or hydroboration of pyridines/quinolines to give the corresponding 1,2- or 1,4-dihydro products . In terms of the cost of metal, the first-row transition metal-based catalytic systems are undoubtedly superior to precious metal-based catalysts (e.g., M = Ru, Rh, Ir) . However, there has been no precedence of the first-row transition metal-based catalytic system for double hydroboration of pyridines.…”
Section: Introductionmentioning
confidence: 99%